Role of palliative care in fetal neurological consultations: Guiding through uncertainty and hope - DonnaMaria E. Cortezzo; DonnaMaria E. Cortezzo; DonnaMaria E. Cortezzo; DonnaMaria E. Cortezzo; Marissa Vawter-Lee; Marissa Vawter-Lee; Abdullah Shoaib; Abdullah Shoaib; Charu Venkatesan; Charu Venkatesan (Frontiers in Pediatrics, 2023)
Fetal neurology is a rapidly evolving and expanding field. Discussions about diagnosis, prognosis, treatment options, and goals of care often begin in the antenatal period. However, there are inherent challenges to fetal counseling of neurological diagnoses due to limitations of fetal imaging, prognostic uncertainty, and variability in neurodevelopmental outcomes. In the midst of uncertainty, families are challenged with preparing a care plan for their baby while simultaneously experiencing profound grief. The paradigms of perinatal palliative care can assist with the grieving process and help frame diagnostic testing and complex decision-making within the context of a family's spiritual, cultural, and social belief system. This ultimately leads to a shared decision-making process and value driven medical care. While perinatal palliative care programs have expanded, many families faced with such diagnoses never meet with a palliative care team prior to delivery. Moreover, there is significant variability in the availability of palliative care services throughout the country. Using an illustrative vignette of a patient with a prenatally diagnosed encephalocele, this review aims to provide a basic framework of perinatal palliative care for fetal neurology diagnoses that emphasizes 1) importance of clear, consistent, and transparent communication among all subspecialists and families, 2) creation of a palliative care birth plan, 3) importance of consistent care providers and longitudinal points of contact prenatally and post-delivery, 4) close communication between the prenatal and post-natal providers to allow for optimal continuity of care, and 5) recognize that information, care plans, and goals of care often evolve over time.